Reexamination of the origin of the pseudo Jahn–Teller puckering instability in silicene1. Issue 12 (28th March 2015) - Soto, J. R.; Molina, B.; Castro, J. J.
<x xml:space="preserve">Abstract</x> The pseudo Jahn–Teller puckering instability in the basic ring unit of silicene is due to the coupling of its ground state with two excited states through the puckering mode.